2019
DOI: 10.1111/jog.13929
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge of and attitudes toward human papillomavirus‐related disease prevention among Japanese: A large‐scale questionnaire study

Abstract: Aim The human papillomavirus (HPV) vaccination rate in Japan fell to nearly 0% following widespread coverage of possible adverse events. Developing a next approach to promote the effective prevention of HPV‐related diseases including cervical cancer (CC) in Japan requires comprehensive understanding of knowledge and attitudes regarding CC prevention, HPV infection and HPV vaccination among the population including laypersons and medical professions in Japan. Methods A questionnaire survey was administered in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
2
22
1
Order By: Relevance
“…In congruence with the German study, studies by Barnard et al . and Suzuki et al . have also determined that males have lower levels of knowledge on HPV than females.…”
Section: Discussioncontrasting
confidence: 75%
“…In congruence with the German study, studies by Barnard et al . and Suzuki et al . have also determined that males have lower levels of knowledge on HPV than females.…”
Section: Discussioncontrasting
confidence: 75%
“…The observations that both genders were aware of HPV's association with cervical cancer, with males having lower awareness, and both genders having limited awareness of HPV causing other cancers, confirms the findings of other studies 16–24. Our cohort’s poor knowledge that HPV causes warts also ratifies other studies 20 22 23…”
Section: Discussionsupporting
confidence: 90%
“…Data were collected using a questionnaire that focused on HPV diseases and vaccination. Although there are validated HPV questionnaires,18 21 we developed a new questionnaire, guided by other questionnaires,21 22 due to the lack of pre-existing questionnaires for male and female 12–13-year-olds that included oral HPV questions. The questionnaire was not designed as a psychometric scale to measure scores on particular constructs; instead it functioned as a series of individual questions, so factor analysis and measures of reliability such as Cronbach’s alpha are not applicable.…”
Section: Methodsmentioning
confidence: 99%
“…Thandar et al (2019) found out, for example, that women had better knowledge and fewer wrong ideas about diseases. Similar results were shown in the research of Suzuki et al (2019), where female had a better knowledge of papillomavirus-related disease and also about prevention of it. The inconsistency between research and other results could lie in the sample size, more concretely in the age of the sample size.…”
Section: Discussionsupporting
confidence: 87%